Genetic Variation and Divergence of Genes Involved in Leaf Adaxial-Abaxial Polarity Establishment in Brassica rapa - Liang, Jianli; Liu, Bo; Wu, Jian; Cheng, Feng; Wang, Xiaowu (Frontiers in Plant Science, 2016)
Alterations in leaf adaxial–abaxial (ad-ab) polarity are one of the main factors that are responsible for leaf curvature. In Chinese cabbage, to form a leafy head, leaf incurvature is an essential prerequisite. Identifying ad-ab patterning genes and investigating its genetic variations will facilitate in elucidating the mechanism underlying leaf incurvature during head formation. In the present study we conducted comparative genomic analysis of the identification of 45 leaf ad-ab patterning genes in Brassica rapa based on 26 homologs in Arabidopsis thaliana, indicating that these genes underwent expansion and were retained after whole genome triplication (WGT). We also assessed the nucleotide diversity and selection footprints of these 45 genes in a collection of 94 Brassica rapa accessions that were composed of heading and non-heading morphotypes. Six of the 45 genes showed significant negative Tajima’s D indices and nucleotide diversity reduction in heading accessions compared to that in non-heading accessions, indicating that these underwent purifying selection. Further testing of the BrARF3.1 gene, which was one of the selection signals from a larger collection, confirmed that purifying selection did occur. Our results provide genetic evidence that ad-ab patterning genes are involved in leaf incurvature that is associated in the formation of a leafy head, as well as promote an understanding of the genetic mechanism underlying leafy head formation in Chinese cabbage.